Viral diversity of Junín virus field strains - Goñi, Sandra Elizabeth (2011)
The Argentine Hemorrhagic Fever, an endemic disease present in a much of Argentina, is caused by the Junín virus (JUNV). Currently, there are sequences available from several strains of this virus, like those belonging to the vaccine lineage (XJ13, XJ#44 and Candid#1), as well as MC2 (rodent isolate) and IV4454 (human isolate). In this article, we report sequence information on two fragments of genomic segment S of viral isolates from the endemic area. A Nested-RT-PCR was used to amplify discrete genomic regions of 13 isolates of rodent and human origin. The bioinformatics studies revealed a great homogeneity of sequences among the JUNV isolates. The phylogenetic classification showed greater evolutionary distance between the old world arenaviruses (Lassa and LCM virus) than between the new world arenaviruses (JUNV and Machupo virus).